Stres akademik pada siswa: Menguji peranan iklim kelas dan school well-being - Muhid, Abdul; Ferdiyanto, Fahmy (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractAcademic stress is a crucial problem experienced by students. Educators and researchers pay high attention to the phenomenon of academic stress among students. This study presents the results of an empirical study of the effects of classroom climate and school well-being on academic stress. This research uses a quantitative approach and is carried out by survey methods that used 3 psychological scales as a measurement tools, namely Academic Stress Scale (? = 0.831); Classroom Climate Scale (? = 0.736); and School Well-being Scale (? = 0.868). The subjects of this study were 105 students taken by the purposive sampling technique at 2 schools. The results showed that simultaneously there was a significant negative effect between classroom climate and school well-being on academic stress. Partially the results of this study indicate that there is a significant influence between classroom climate on academic stress. While the school well-being variable has a significant negative effect on academic stress. Classroom climate and school well-being variables can be used as strong predictors of academic stress.Keywords: Academic stress; Classroom Climate; Cchool Well-Being AbstrakStres akademik menjadi permasalahan yang krusial dialami oleh siswa. Para pendidik dan peneliti menaruh perhatian yang tinggi terhadap fenomena stres akademik di kalangan siswa. Penelitian ini memaparkan hasil studi empiris tentang pengaruh iklim kelas dan school well-being terhadap stres akademik. Penelitian ini menggunakan pendekatan kuantitatif dan dilakukan dengan metode survei yang menggunakan 3 skala psikologi sebagai alat ukur, yaitu Skala Stres Akademik (? = 0.831); Skala Iklim Kelas (? = 0.736); dan Skala School Well-being (? = 0.868). Subyek penelitian ini berjumlah 105 siswa yang diambil dengan teknik purposive sampling pada 2 sekolah. Hasil penelitian menunjukkan bahwa secara simultan ada pengaruh negatif yang signifikan antara iklim kelas dan school well-being terhadap stres akademik. Secara parsial hasil penelitian ini menunjukkan bahwa ada pengaruh yang signifikan antara iklim kelas terhadap stres akademik. Sedangkan variabel school well-being memiliki pengaruh negatif yang signifikan terhadap stres akademik. Variabel iklim kelas dan school well-being dapat dijadikan prediktor yang kuat terhadap stres akademik.Kata kunci: Iklim Kelas; School Well-Being; Stres Akademik